2020
DOI: 10.1111/ajo.13249
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being, obstetrics and gynaecology and COVID‐19: Leaving no trainee behind

Abstract: The COVID‐19 pandemic has significantly disrupted training in obstetrics and gynaecology. Past pandemics have been shown to result in significant psychological morbidity. As specialty trainees continue frontline work, they will face unprecedented work environments and may face delays in progression due to postponed examinations, case log shortfalls and inadequate clinical rotations. This contributes to burnout, anxiety and depression. We share technology‐based suggestions as well as institutional, departmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The experiences of healthcare workers have been examined in other countries 11. Early on in the COVID-19 pandemic, a qualitative study from Wuhan, China,5 showed that the intensive work during the pandemic drained healthcare workers physically and emotionally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences of healthcare workers have been examined in other countries 11. Early on in the COVID-19 pandemic, a qualitative study from Wuhan, China,5 showed that the intensive work during the pandemic drained healthcare workers physically and emotionally.…”
mentioning
confidence: 99%
“…The experiences of healthcare workers have been examined in other countries 11. Early on in the COVID-19…”
mentioning
confidence: 99%
“…Pregnant women with risk factors (advanced maternal age, obesity, diabetes, hypertension, solid organ transplant, immunosuppression, sickle cell disease, chronic lung, kidney or heart disease 27 , 117 , 138 , 139 , 140 ) or high exposure risks (healthcare workers, drivers, cleaners or residential home carers) 121 , 122 , 126 , 141 may be prioritised for early vaccination. Healthcare workers are within the highest WHO SAGE Stage 1 vaccine priority 112 and women comprise about 70% of that workforce, 142 a large proportion being of reproductive age.…”
Section: Recommendationsmentioning
confidence: 99%
“…About half the articles were related to undergraduate medical education [445][446][447][448][449][450][451][452][453][454][455][456][457][458], such as the switch to online learning [446][447][448][449][450]452,453,455,456] and resuming clinical placements [454,458] in an attempt to minimise the disruption to clinical learning. The remaining half were about residency training [459][460][461][462][463][464][465][466][467][468][469][470][471][472][473][474], which explored the impact of the pandemic on various specialties' training programmes [462][463][464][465][466]468,46...…”
Section: Medical Education (30 Articles)mentioning
confidence: 99%